Pelatihan dan Pendampingan Guru dalam Mengembangkan Materi Pembelajaran Berbasis Teknologi Informasi di Pesantren - Syaifudin Zuhri; Aries Musnandar (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to enhance teachers’ competence in developing information technology–based learning materials within the Islamic boarding school context. The training and mentoring program was conducted at Pondok Pesantren Sirojul Ulum over a period of one month, involving ten teachers from various subjects. The research employed a participatory approach consisting of training sessions, implementation mentoring, and performance evaluation. During the program, participants received training on the use of digital tools, the development of instructional media using applications such as PowerPoint, Canva, and Google Classroom, as well as the creation of interactive learning videos. The results indicated a significant improvement in teachers’ ability to design and utilize digital learning media independently. Approximately 80% of participants successfully produced functional digital learning products, while all participants demonstrated improved digital literacy, as observed and assessed through interviews. Moreover, continuous mentoring fostered teachers’ motivation and creativity in integrating technology to create more engaging and student-centered learning experiences. In conclusion, the training and mentoring program effectively strengthened teachers’ digital competencies in Islamic boarding schools. Similar initiatives are recommended to be implemented continuously with institutional support and adequate infrastructure to promote inclusive and adaptive digital transformation in Islamic education. Keywords: Teacher Training, Mentoring, Information Technology, Islamic Boarding School, Learning Media